2014
DOI: 10.1080/21623996.2014.999503
|View full text |Cite
|
Sign up to set email alerts
|

Role of STAT3 in lung cancer

Abstract: Lung cancer remains a challenging disease. It is responsible for the high cancer mortality rates in the US and worldwide. Elucidation of the molecular mechanisms operative in lung cancer is an important first step in developing effective therapies. Accumulating evidence over the last 2 decades suggests a critical role for Signal Transducer and Activator of Transcription 3 (STAT3) as a point of convergence for various signaling pathways that are dysregulated in the disease. In this review, we discuss possible m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 124 publications
4
64
1
1
Order By: Relevance
“…Recent studies have reported activation of the JAK/STAT pathway in sex-determining region Y box 2 (SOX2)-driven, LKB1-deficient mouse model of squamous cell lung cancer (47) and increase of IL-6 production and subsequent activation of STAT3 in LKB1-deficient mouse model of LADC (48,49). As IL-6/JAK/STAT signaling axis plays important roles in cell proliferation, survival, invasion, chemoresistance, and immunosuppression, (48,(50)(51)(52)(53), targeting CPS1 might alter tumor microenvironment and improve efficiency of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported activation of the JAK/STAT pathway in sex-determining region Y box 2 (SOX2)-driven, LKB1-deficient mouse model of squamous cell lung cancer (47) and increase of IL-6 production and subsequent activation of STAT3 in LKB1-deficient mouse model of LADC (48,49). As IL-6/JAK/STAT signaling axis plays important roles in cell proliferation, survival, invasion, chemoresistance, and immunosuppression, (48,(50)(51)(52)(53), targeting CPS1 might alter tumor microenvironment and improve efficiency of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, activation of STAT3 and NF-κB are frequently observed and their roles have been analyzed experimentally [12][13][14][15][16] . Moreover, STAT3 and ELK-1 are activated by EGFR (epidermal growth factor receptor) 13,14 .…”
mentioning
confidence: 99%
“…In lung cancer, activation of STAT3 and NF-κB are frequently observed and their roles have been analyzed experimentally [12][13][14][15][16] . Moreover, STAT3 and ELK-1 are activated by EGFR (epidermal growth factor receptor) 13,14 . In addition, a recent report has shown that expression of a microRNA, which directly suppresses MCL1 mRNA, is suppressed in lung cancer 17 , suggesting that MCL1 mRNA expression is activated by transcriptional and post-transcriptional regulation in lung cancer.…”
mentioning
confidence: 99%
“…STAT3 is a member of the STAT protein family, which is phosphorylated by the receptor-associated kinases in response to cytokines and growth factors, and then forms heterodimers that translocate to the cell nucleus where they function as transcription activators. It has been widely reported that STAT3 play significant roles in the cell growth, EMT, oncogenic transformation, tumorigenesis, progression and immune evasion of lung cancer [46][47][48]. The E2F1 transcription factor is realized as a regulator of the cell cycle as well as a potent mediator of DNA damage-induced apoptosis and the checkpoint response.…”
Section: Discussionmentioning
confidence: 99%